Metafysikeren Løgstrup - Widmann, Peter (Religionsvidenskabeligt Tidsskrift, 1985)
The final work of the late Knud Ejler Løgstrup Metafysik I-IV can be considered as a consequent step on his road to a religious philosophy. In all his writings Løgstrup has tried to show the importance of a religious interpretation of reality both for a sound development of theology and for the survival of Western civilization. This religious interpretation has to be pronounced as a philosophical position, criticizing the disastrous consequences of the split between nature and human existence in modern philosophy. This return to religion in the understanding of reality is not meant to eliminate modern science of the liberties of Western society. According to Løgstrup, the interpretation of reality as given by a transcendent power is a possibility – not a necessity – also today. This interpretation does not touch the radical otherness of God, whose only unambiguous manifestation is to be found in his Word in Christ. The article raises some questions concerning the consistency of Løgstrup’s metaphysical and theological position. In the posthumously edited volume III, Løgstrup claims that the “Universe” is the final actor in both nature and history. Is this position tenable without traditional realistic metaphysics? Does Løgstrup rely on a pre-critical pre-supposition, namely that we have access to reality as such? Løgstrup seems, consequently, to exaggerate the dangers of post-critical thinking. Furthermore, it can be questioned, whether Løgstrups’ latest metaphysical views are in harmony with some of his theological convictions.